Essential Oil Disinfectant Efficacy Against SARS-CoV-2 Microbial Surrogates - Bailey, Emily S.; Curcic, Marina; Biros, Jnev; Erdogmuş, Hüseyin; Bac, Nurcan; Sacco, Albert (Frontiers in Public Health, 2021)
Reports of COVID-19 cases potentially attributed to fomite transmission led to the extensive use of various disinfectants to control viral spread. Alternative disinfectants, such as essential oils, have emerged as a potential antimicrobial. Four essential oil blends were tested on three different surfaces inoculated with a coronavirus surrogate, bacteriophage Phi 6, and a bacterial indicator, Staphylococcus aureus. Log10 concentration reductions were analyzed using GraphPad Prism software. Data collected in this study show that the application of dilute essential oil disinfectants using a spray delivery device is an effective way to reduce concentrations of bacterial and viral microorganisms on ceramic, stainless steel, and laminate surfaces. Surrogate viruses were reduced up to 6 log10 PFU and bacterial were reduced up to 4 log10 CFU. Although surfaces are no longer considered a high risk fomite for COVID-19 transmission, the disinfection of microorganisms on surfaces remains an important consideration for high touch areas in hospitals, waiting rooms, etc. The application of spray disinfectants, based on essential oil blends, provides a rapid and effective means to reduce microbial contamination on high-touched surfaces.